Assessment on Water Quality and Trace Metal Concentrations of an Urban Lake in Kuching Reservoir Park - Diana Chendai, Ngadan (University Malaysia Sarawak, UNIMAS, 2015)
A study of the water quality and trace metal concentrations of an urban lake in Kuching Reservoir Park (or known as Taman Budaya) was conducted for three months, from October 2014 to December 2014. Four sampling stations were selected to represent the open water body in the lake. A total of 16 water quality parameters and 5 trace metals were measured and compared as stipulated in the Malaysian Department of Environment - Water Quality Index (DOE-WQI). In addition, classification according to the Interim National Water Quality Standard (INWQS) was applied. With respect to INWQS, the mean values of physical and chemical variables were temperature: 29.76±0.29 oC; pH: 7.69±0.22; dissolved oxygen (DO): 5.07±0.39 mg/L; total suspended solids (TSS): 204±167.68 mg/L; total dissolved solids (TDS): 84.78±7.47 mg/L; turbidity: 53.8±12.10 NTU; biological oxygen demand (BOD): 1.13 ±0.20 mg/L; chemical oxygen demand (COD): 21.5±0.20 mg/L; nitrite: 0.09±0.02 mg/L; nitrate: 1.0 ±0.28 mg/L; and ammoniacal-nitrogen (AN): 0.05±0.02 mg/L were within the normal range of Class IIB for recreational purposes with an exception of concentration in the lake. Whereas trace metals concentrations were in decreasing order: zinc>manganese>lead>chromium>arsenic. Results showed that based on Malaysian WQI, the lake water status in Kuching Reservoir Park is classified as Class III with the mean value of 65.30, which is considered as moderate water quality. Recommended best management practices (BMPs) are phosphorus removal by using alum as the chemical precipitant, lake flushing and aeration by the adaptation of floating fountain. Three aspects of lake management involving the public’s participation and awareness, institutional cooperation between DBKU as the main authority and research institutions as well as better enforcement by the legislative were crucially emphasized.